A COMPARISON OF THE LOSS OF CO AND CO2 DURING COALIFICATION - Kopp O.C.; Bennett M.E. (My University, 2001)
We recently published the results of a study of volatiles evolved during coalification (Kopp et al.,.2000) based on the loss of CH4, H2O, and CO. At that time, the loss of CO2 was not modelled because low-rank lignites and subbituminous coals (which we considered to be those ranks most likely to lose CO2) were not included in our model; however, both reviewers of the manuscript asked how the release of CO2 would influence the results of our model. The purpose of this Short communication is to add infor-mation about the loss of CO2 and to compare the results of a model based on CH4, H2O, and CO2 with our previous model based on the loss of CH4, H2O and CO. Both models make use of information2obtained from the US Geological Survey Coal Quality (COALQUIL) database.